People in more individualist cultures are more motivated to make others feel better - Shir Ginosar Yaari; Yulia Chentsova-Dutton; Michaela Riediger; Antje Rauers; Min Young Kim; Yuri Miyamoto; Allon Vishkin; Julia Anne Freitag; Jan Cieciuch; Mariana Gurevich; Maria Padun; Nevin Solak; et al. (Proceedings of the National Academy of Sciences, 2026)
In many Western cultures, trying to make others feel better is considered critical for psychological health and social relationships. However, given that people think about emotions and relationships differently across cultures, the desirability, means, and benefits of making others feel better may also vary by culture. In two multicountry survey studies (Study 1: N = 3,154, 13 countries; Study 2: N = 3,503, 17 countries) and in a daily dairy study (Study 3: N = 243, 2 countries), we assessed motivation and strategies used for influencing others’ and one’s own emotions. To test whether potential cross-cultural differences in motivation and strategies in emotion regulation are unique to social interactions, we compared cultural differences in making others feel better to making oneself feel better. Across studies, cultural differences in influencing others’ emotions were greater than those in influencing one’s own emotions. Members of more individualist (vs. collectivist) cultures were more motivated to make others (but not themselves) feel better, were more likely to express care and less likely to encourage others to suppress their emotions or to ruminate. These patterns, in turn, were linked to an index of relationship closeness in an individualist (but not a collectivist) culture. These findings suggest that helping others feel better may not be equally desirable across cultures.